Lung cancer mortality reduction by LDCT screening: results from the randomized German LUSI trial - Becker, Nikolaus; Motsch, Erna; Trotter, Anke; Heußel, Claus Peter; Dienemann, Hendrik; Schnabel, Philipp Albert; Kauczor, Hans-Ulrich; González Maldonado, Sandra; Miller, Anthony B.; Kaaks, Rudolf; Delorme, Stefan (International journal of cancer, 2020)
In 2011, the U.S. National Lung Cancer Screening Trial (NLST) reported a 20% reduction of lung cancer mortality after regular screening by low-dose computed tomography (LDCT), as compared to X-ray screening. The introduction of lung cancer screening programs in Europe awaits confirmation of these first findings from European trials that started in parallel with the NLST. The German Lung cancer Screening Intervention (LUSI) is a randomized trial among 4,052 long-term smokers, 50-69 years of age, recruited from the general population, comparing five annual rounds of LDCT screening (screening arm; n = 2,029 participants) with a control arm (n = 2,023) followed by annual postal questionnaire inquiries. Data on lung cancer incidence and mortality and vital status were collected from hospitals or office-based physicians, cancer registries, population registers and health offices. Over an average observation time of 8.8 years after randomization, the hazard ratio for lung cancer mortality was 0.74 (95% CI: 0.46-1.19; p = 0.21) among men and women combined. Modeling by sex, however showed a statistically significant reduction in lung cancer mortality among women (HR = 0.31 [95% CI: 0.10-0.96], p = 0.04), but not among men (HR = 0.94 [95% CI: 0.54-1.61], p = 0.81) screened by LDCT (pheterogeneity = 0.09). Findings from LUSI are in line with those from other trials, including NLST, that suggest a stronger reduction of lung cancer mortality after LDCT screening among women as compared to men. This heterogeneity could be the result of different relative counts of lung tumor subtypes occurring in men and women.
Online 4 Jun 2019
Gesehen am 15.04.2020